gC1qR/HABP1/p32 Is a Potential New Therapeutic Target Against Mesothelioma - Peerschke, Ellinor; Stier, Kenneth; Li, Xiaoyu; Kandov, Evelyn; de Stanchina, Elisa; Chang, Qing; Xiong, Yuquan; Manova-Todorova, Katia; Fan, Ning; Barlas, Afsar; Ghebrehiwet, Berhane; Adusumilli, Prasad S. (Frontiers in Oncology, 2020)
Mesothelioma is an aggressive cancer of the serous membranes with poor prognosis despite combination therapy consisting of surgery, radiotherapy, and platinum-based chemotherapy. Targeted therapies, including immunotherapies, have reported limited success, suggesting the need for additional therapeutic targets. This study investigates a potential new therapeutic target, gC1qR/HABP1/p32 (gC1qR), which is overexpressed in all morphologic subtypes of mesothelioma. gC1qR is a complement receptor that is associated with several cellular functions, including cell proliferation and angiogenesis. In vitro and in vivo experiments were conducted to test the hypothesis that targeting gC1qR with a specific gC1qR monoclonal antibody 60.11 reduces mesothelioma tumor growth, using the biphasic mesothelioma cell line MSTO-211H (MSTO). In vitro studies demonstrate cell surface and extracellular gC1qR expression by MSTO cells, and a modest 25.3 + 1.8% (n=4) reduction in cell proliferation by the gC1qR blocking 60.11 antibody. This inhibition was specific for targeting the C1q binding domain of gC1qR at aa 76-93, as a separate monoclonal antibody 74.5.2, directed against amino acids 204-218, had no discernable effect. In vivo studies, using a murine orthotopic xenotransplant model, demonstrated an even greater reduction in MSTO tumor growth (50% inhibition) in mice treated with the 60.11 antibody compared to controls. Immunohistochemical studies of resected tumors revealed increased cellular apoptosis by caspase 3 and TUNEL staining, in 60.11 treated tumors compared to controls, as well as impaired angiogenesis by decreased CD31 staining. Taken together, these data identify gC1qR as a potential new therapeutic target against mesothelioma with both antiproliferative and antiangiogenic properties.